The Effects of Health Anxiety and Litigation Potential on Symptom Endorsement, Cognitive Performance, and Physiological Functioning in the Context of a Food and Drug Administration Drug Recall Announcement - Lecci, Len; Page, Gary Ryan; Keith, Julian R.; Neal, Sarah; Ritter, Ashley (Frontiers in Psychology, 2022)
Drug recalls and lawsuits against pharmaceutical manufacturers are accompanied by announcements emphasizing harmful drug side-effects. Those with elevated health anxiety may be more reactive to such announcements. We evaluated whether health anxiety and financial incentives affect subjective symptom endorsement, and objective outcomes of cognitive and physiological functioning during a mock drug recall. 161 participants reported use of over-the-counter pain medications and presented with a fictitious medication recall via a mock FDA website. The opportunity to join a class-action lawsuit was manipulated. We assessed health anxiety, recalled drug usage, blood pressure, heart rate, and performance on a computerized Trail Making Test (TMT). Symptom endorsement was strongly predicted by health anxiety. When combined, three health anxiety measures explained 28.5% variance (Cohen's d = 1.26). These effects remain strong after controlling for depression and anxiety. Litigation condition did not predict symptom endorsement. Blood pressure and heart rate were modestly predicted by health anxiety, but not by litigation condition. TMT performance was consistently predicted by health anxiety, with higher scores associated with poorer performance. Although there were no main effects for litigation, interactions consistently emerged for the TMT, with generally poorer performance for those with higher health anxiety in the non-litigation condition; whereas health anxiety was unrelated to performance for the litigation condition. All but one participant joined the litigation when given the opportunity, despite a healthy sample and minimal use of pain medication. Subsequent data from 67 individuals with no mention of the FDA scenario or litigation showed that health anxiety still significantly predicts symptom endorsement (12.6% variance), but the explained variance is less than half that obtained in the FDA scenario. The findings suggest that health anxiety plays a significant role in adverse symptom reporting, beyond anxiety or depression, and this effect is independent of the presence of the FDA recall. The lack of differences for health anxiety and symptom endorsement between litigation and non-litigation conditions rules out malingering. Although it is general practice in drug recalls to list potential adverse side effects caused by medications, this may elicit unintended symptom experiences and health anxious individuals may be more susceptible.